What's in a diagnosis: The effect of externalizing and internalizing students' behaviour on pre‐service teachers' classroom management and interaction strategies. (7th March 2021) - Glock, Sabine; Pit‐ten Cate, Ineke M.
Abstract : Background: All over the word, classrooms are getting more and more diverse and teachers are required to effectively manage these classes even when students have special education needs (SEN). Aims: The study aimed to investigate classroom management strategies and interpersonal teacher behaviour in relation to students internalizing and externalizing behaviour, whereby we varied the diagnosis of special educational needs. Sample: Two hundred and fifty‐four German pre‐service teachers (143 female) with a mean age of 26.04 years participated in the study. Method: Using an experimental between‐subjects design, a fictitious student was described as exhibiting either internalizing or externalizing behaviour. Additionally, we varied whether the student was diagnosed as having SEN or not. The participants were asked to indicate which strategies they would apply and how they would interact with students. Results: Results showed that teacher interaction in response to both students with internalizing and externalizing behaviour approached ideal interpersonal teacher behaviour (i.e. high level of cooperativeness with certain level of dominance), whereas pre‐service teachers applied all classroom management strategies to minimize effects of student behaviour on learning time. Although pre‐service teachers adapted their responses based on type of behaviour, they only made allowances for internalizing behaviour while their response to externalizing behaviour did not vary much as a function of a SEN diagnosis. Conclusions: Together, these findings highlight the importance of providing pre‐service teachers with the pedagogical knowledge concerning effective classroom management and flexible use of strategies in response to diverse student needs in inclusive classrooms.